Two-stage binding of a protein to the polyanion: Non-denaturing interaction followed by denaturation. (18th May 2015) - Semenyuk, Pavel; Orlov, Victor; Muronetz, Vladimir; Izumrudov, Vladimir
Abstract: Synthetic polyelectrolytes are increasingly used for gene and drug delivery as well as for protein immobilization and preventing protein aggregation. Polysulfoanions are the most efficient suppressors of the aggregation but have the adverse effect on structure and activity of the bound enzyme. We revealed factors that control denaturation of model positively charged enzyme glyceraldehyde-3-phosphate dehydrogenase in presence of polysulfoanions and polyphosphate anions differed by degree of polymerization. The two-stage process occurred on the protein titration with polyanion. The protein structure remained practically intact up to the end of the first stage, whereas further titration on the second stage resulted in protein denaturation. The molar ratio polyanion/protein corresponding to onset of the second stage increased with elongation of chains and eventually it disappeared for highly polymerized polyanions which did not denature the protein. Elucidation of the factors caused denaturation is relevant for modeling interaction of proteins with natural polyelectrolytes. Graphical abstract: Highlights: Protein titration with polyanion is accompanied with two-stage heat release. The protein structure remains intact up to the end of the first stage. The second stage results in protein denaturation. The longer are charged chains, at the higher molar ratio the second stage starts.